Hauling molasses by spider. Barbados, B. W. I. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2024)
This image shows workers pulling carts called “Spiders”, which have puncheons or what is commonly called a barrel attached. This device was used for making it easier to move a puncheon of molasses or rum using only the power of human muscles. These puncheons are filled with molasses for shipping to other countries. There are a number of male workers hauling and organizing the barrels. There is an ad for “Veedol - the lubricant that resists heat” located on the side of the store. There is also a tractor with the licensed number #0124 visible on the street. This is a divided back postcard. Back of the Postcard CMNTD £22 (Handwritten in Pencil)
Landscape, Black & White, 3 ½” x 5½ “
Keywords: Barrels; Laborer; Carts and wagons; Sugar industry; Molasses; Puncheons; Spiders; Workers; Careenage